Knowledge, perceptions, and attitudes toward complementary and alternative medicines among pharmacy students of a Malaysian public university - Jamshed, Shazia; Umair Khan, Muhammad; Ahmad, Akram; Elkalmi, Ramadan Mohamed Mahmod (Wolters Kluwer ‑ Medknow, 2016)
The use of complementary and alternative medicine (CAM) is consistently on the rise worldwide. Consumers often consider pharmacists as a major source of information about CAM products and their safety. Due to the limitation of data, it is worth exploring the knowledge, perceptions, and attitudes of pharmacy students toward CAM. Objective: The objective of this study was to explore the knowledge, perceptions, and attitudes of pharmacy students regarding the use of CAM in Malaysia. Materials and Methods: A cross‑sectional study was conducted for 3 months among Bachelor of Pharmacy students in a public sector University of Malaysia. A pretested, self‑administered questionnaire, comprised four sections, was used to collect the data from 440 participants. Descriptive analysis was used, and Chi‑square test was used to test the association between dependent and independent variables. Results: Of 440 questionnaire distributed, 287 were returned giving a response rate of (65.2%). The results showed that 38.6% participants gave correct answers when asked about the use of herbal products with digoxin. Majority of the participants were knowledgeable about supplementary therapy (25.3%) while the lack of knowledge was mostly evident in traditional Chinese medicines (73.7%). Majority of the students were either neutral (49.5%) or disagreed that (42.8%) CAM use is unsafe. Females were more in disagreement to the statements than males (P = 0.007). Majority of students also agreed to use CAM therapies for their health and well‑being (51.2%). Conclusion: The study revealed that pharmacy students did not have adequate knowledge of CAM though their attitudes and perceptions were relatively positive.